ANALYSIS OF INDUSTRIAL WASTE WITH BINDING PROPERTIES - Akmaljon Khakimov; Nasiba Vokhidova (Academia Science Repository, 2023)
The results of briquetting technology and composition development of low-quality lignite waste using waste modified with mechanically activated organo-mineral binders as a binder are presented.